THE EFFICACY OF SIDDHA MEDICINE BRAMI NEI WITH VARMA THERAPY IN MANTHA SANNI (AUTISM SPECTRUM DISORDER) IN CHILDREN – A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2018)
Mantha Sanni (Autism) is a Mukkuttra disease that is imbalance of all the three main fundamental principles of Vatham, Pitham and Kabam. Mantha Sanni is a neuro developmental disorder typically appearing in the first one and half years of life and characterised by impaired social and communication skills.. In the all over the world, the surveillance study identified 1 in 68 children suffering with ASD. In India, the prevalence ratio is 1:46. It is about 4.5 times more common among boys (1:48) than among girls (1:189). The higher prevalence rate was observed in the rural area. Socioeconomic status may be one of the fundamental indicators for ASD in India. Autism spectrum disorder is the world most common disorder in Children. In this study, I have to present 3 case reports of ASD children based on the assessment scale. The main course of treatment are Brami Nei as internal and Varmam as External therapy in the recommended dose as per Siddha pharmacopeia for 3 months. After 3 months, ASD children improve the cognitive skills and eye to eye contact Hyperactivity reduced well. Most of the formulation acting on psyche is ghee based. It is well established that the drugs to have its action on brain should have the capacity to cross the blood brain barrier and for the purpose ghee based Brahmi Nei is recommended for ASD in children. Manipulative therapy like Varma is to enhance the mind calming activity with sound sleep, good eye to eye contact and to reduce anxiety, hyperactivity. All the ingredients in both Internal medicines are herbal. So my attorney has to conclude the Siddha management therapy might be good and safest. It will be definitely efficacy in treating ASD children. Hence, Brami Nei as internal Varmam as External therapy may have a role to curing the ASD children.